Clostridium difficile isolates derived from Czech horses are resistant to enrofloxacin; cluster to clades 1 and 5 and ribotype 033 predominates - Kecerova, Zuzana; Cizek, Alois; Nyc, Otakar; Krutova, Marcela (Anaerobe, 2019)
Clostridium difficile has been recovered from the faeces of several animal species as well as horses. Between April 2015 and October 2016, 213 samples of faeces from non-hospitalized (n = 138) and hospitalized horses (n = 75) were investigated and eighteen C. difficile isolates were cultured using an enrichment method. Sixteen C. difficile positive samples were identified from hospitalised horses (p < 0.01). Molecular typing revealed seven ribotypes and sequence types (RT033/ST11 n = 8, 44.4%; RT081/ST9 n = 4, 22.2%; RT009/ST3 n = 2, 11.1%; RT003/ST12 n = 1, 5.6%; RT010/ST15 n = 1, 5.6%; RT012/ST54 n = 1, 5.6%; RT039/ST26 n = 1, 5.6%). Seven identified STs clustered to two clades (1 and 5). All C. difficile isolates were susceptible to amoxicillin, metronidazole, moxifloxacin, and vancomycin. One isolate (RT039) exhibited a high level of resistance to erythromycin and clindamycin (256 mg/L) and carried the ermB, adenine methylase gene. Five isolates were resistant to clindamycin at lower minimal inhibitory concentrations (MICs = 8-16 mg/L) and were susceptible to erythromycin and also ermB negative. All isolates were resistant to enrofloxacin (MICs ranged between 4 and 32 mg/L). Eight isolates were resistant to tetracycline (MICs 12-32 mg/L). Of them, four isolates carried the tetM gene and four isolates the tetW gene. In addition, the tetracycline resistance determinants identified were: tetA (P) (n = 4); tetB (P); and tetL (n = 1 each). The presence of tetW or tetM, together with other tet-class mechanisms, lead to an increase in the MICs to tetracycline. C. difficile isolates derived from Czech horses are identical to the ribotypes identified in humans and carry acquired antimicrobial resistance genes whose dissemination from veterinary healthcare sector to humans should be monitored by the "One health" approach.
Keywords: Tetracycline resistance; horses; Cluster Analysis; Genotype; tetW; Česká republika; Sequence Analysis, DNA; antibakteriální látky; Clostridium difficile; sekvenční analýza DNA; Microbial Sensitivity Tests; shluková analýza; Clostridioides difficile; Ribotype 033; Czech Republic; enrofloxacin; Animals; Genes, Bacterial; Clade 1; Anti-Bacterial Agents; MLST; zvířata; Ribotyping; mikrobiální testy citlivosti; Horses; koně; Clade 5; genotyp; tetM; Enrofloxacin; ribotypizace; bakteriální geny